2008
DOI: 10.1002/prot.21972
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the residue–residue coevolution network and the functionally important residues in proteins

Abstract: It is a common belief that some residues of a protein are more important than others. In some cases, point mutations of some residues make butterfly effect on the protein structure and function, but in other cases they do not. In addition, the residues important for the protein function tend to be not only conserved but also coevolved with other interacting residues in a protein. Motivated by these observations, the authors propose that there is a network composed of the residues, the residue-residue coevoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…Coevolving residues tend to be spatially coupled and correspond to functionally important sites exhibiting correlated and compensatory mutations in homologous proteins [113]. These residues could also form networks with connections corresponding to coevolutionary interaction strengths between nodes, where the underlying small-world topology of such networks is similar to the structure-based residue interaction networks [114116]. Furthermore, coevolving residues can assemble into structurally stable and quasi-independent modules of physically interacting residues termed ‘protein sectors’ [103,104].…”
Section: Introductionmentioning
confidence: 99%
“…Coevolving residues tend to be spatially coupled and correspond to functionally important sites exhibiting correlated and compensatory mutations in homologous proteins [113]. These residues could also form networks with connections corresponding to coevolutionary interaction strengths between nodes, where the underlying small-world topology of such networks is similar to the structure-based residue interaction networks [114116]. Furthermore, coevolving residues can assemble into structurally stable and quasi-independent modules of physically interacting residues termed ‘protein sectors’ [103,104].…”
Section: Introductionmentioning
confidence: 99%
“…Combining the outcome of several prediction methods into a consensus prediction (termed HelixCorr), this fraction could be further increased to more than 55%. Recent publications analyzing co-evolving residues already highlighted that residue co-evolution may have other than structural reasons (Gloor et al 2005;Lee et al 2008). Th e results obtained with HelixCorr additionally indicated that coevolution not only occurs to maintain specifi c amino acids required for a structural contact but also infl uences the correct formation of a helix-helix contact by aff ecting its sequence context.…”
Section: Co-evolving Residues In Membrane Proteinsmentioning
confidence: 77%
“…This fact has been exploited to infer the structural factor such as interresidue contacts [13] and to evaluate the correctness of de novo model [28]. Recently, it has been also shown that key residues can be identified by analyzing residue-residue coevolution network [29].…”
Section: Discussionmentioning
confidence: 99%